Domestic stakeholders’ aspirations for mou renewal on women migrant workers in Malaysia - Mindarti, Lely Indah; Saleh, Choirul; Maskur, Ali (Faculty of Communications Science, Dr. Soetomo University, 2021)
The research was focused on investigating the collaborative process between stakeholders and the differences in the two countries’ interests. This qualitative research was a case study with content analysis and descriptive techniques. The data collection techniques used were in-depth interviews with relevant stakeholders and document collection. The study results indicate that all stages have been carried out in the collaboration process, starting from face-to-face, building trust, negotiation and discussion, and commitment. However, the differences in the two countries’ interests are also clearly visible, such as the Government of Indonesia prioritising the placement and protection of migrant workers and prioritising the protection of users (employers) and International Domestic Migrant Workers (employees or Indonesian Domestic Migrant Workers) in Malaysia.